CHOICE ARCHITECTURE FOR DRIVING APP ADOPTION: STRATEGIES TO INCREASE CONSUMER INTEREST IN MOBILE APPLICATIONS - Aripin, Zaenal; Adi Wibowo, Lili; Ariyanti, Maya (Organisasi Kreatif Indonesia Emas, 2024)
In the ever-evolving digital era, the choice of application architecture plays an important role in the success of a mobile application. This research investigates the technical factors that influence the choice of application architecture and their impact on adoption and consumer interest in mobile applications. Factors such as security, flexibility, and scalability are analyzed in the context of user preferences and industry trends. Through a literature review, a qualitative literature study was used to gain an in-depth understanding of how these technical factors influence the choice of application architecture and its impact on the user experience. The results show that users tend to prefer application architectures that provide a responsive, consistent, and secure user experience. Microservicing and service-based (SOA)-like architectures are often chosen for their ability to provide high levels of flexibility, interoperability, and security. Additionally, developers can also use knowledge about user preferences for certain application architectures to design applications that are more attractive and relevant to consumers. By following trends and adopting an approach that fits user needs, developers can increase user adoption and retention, and ensure the long-term success of their apps in an increasingly competitive market.